PENERAPAN KONSELING RET UNTUK MENINGKATKAN MOTIVASI STUDI LANJUT PERGURUAN TINGGI SISWA KELAS XII PERUMAHAN GONDANGMANIS - Rizqi Atsmarina Ulfa; Susilo Rahardjo; Nur Mahardika (Jurnal Muria Research Guidance and Counseling (MRGC), 2022)
The purpose of this study was to find out what factors influence intrinsic and extrinsic motivation for further study to higher education in class XII students of Gondangmanis Housing RT 08 and to find out whether RET can increase the motivation for further study of adolescents to college in class XII students of Gondangmanis Housing RT 08. This research is a case study research and it was conducted in three counseling sessions. Data collection techniques used are observation, interviews, and documentation.The results showed that the factors causing the low motivation for further studies to university experienced by MW and MF were intrinsic factors, namely irrational thinking patterns towards college and both parents. While the extrinsic factors are the bad experience of relatives, the family economy and the lack of direction from the parents for higher education. Both counselees showed increased motivation to continue their studies at higher education.